Seroprevalence of Hepatitis B, C Virus and HIV in Behcet's Disease Living in Usak Region - Etem, Arzu Akagac; Etem, Ebru Onalan; Dogan, Guliz Toklu; Yildirmak, Sembol Turkmen; Oz, Isil (Derman Medical Publ, 2013)
Aim: Our purpose to compare hepatitis B, C and HIV viruses seroprevalance in Behcet's Disease (BD) and control group and to associate with BD. Material and Method: 56 case who had diagnosed with International Study Group for BD and 56 healthy controls were inculeded in this study. Serological markers of HBsAg, anti-HBsAg, anti-HCV and anti-HIV were studied with chemiluminescence method in both groups. Pearson chi-square test was used for statistical analyze. Results: There was statistically no difference between the two groups respect to HBsAg, Anti-HBsAg, anti-HCV and anti-HIV serological evidence (p=0,154, p=0,468, p=1,000, p=1,000 respectively). Discussion: Serological evidence of previous HBV, HCV and HIV infection was not significantly different between BD and control groups. However HBsAg was found in 2 BD patients as compared with none of the healthy controls. Although our findings indicate that the association of BD and HBV and HCV fortuitous, we are thinking that a larger series is still needed.
Uşak yöresinde yaşayan behçet hastalarında hepatit B, C ve HIV seroprevelansı
Keywords: Behcet's Disease; Hepatitis B Virus; Hepatitis C Virus; Human Immune Deficiency Virus